2022
DOI: 10.1161/jaha.121.024393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multisystem Inflammatory Syndrome in Children–Related Myocarditis, Classic Viral Myocarditis, and COVID‐19 Vaccine‐Related Myocarditis in Children

Abstract: Background Although rare, classic viral myocarditis in the pediatric population is a disease that carries significant morbidity and mortality. Since 2020, myocarditis has been a common component of multisystem inflammatory syndrome in children (MIS‐C) following SARS‐CoV‐2 infection. In 2021, myocarditis related to mRNA COVID‐19 vaccines was recognized as a rare adverse event. This study aims to compare classic, MIS‐C, and COVID‐19 vaccine‐related myocarditis with regard to clinical presentation, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 24 publications
4
51
0
1
Order By: Relevance
“…In our comparison, the classic myocarditis group had a higher burden of LGE than the C-VAM group at intermediate term follow-up. These findings suggest the possibility of a more favorable prognosis in children with C-VAM as opposed to classic myocarditis and extend earlier findings from our group comparing early clinical outcomes among patients with C-VAM, classic myocarditis, and MIS-C(12). The pattern of LGE at intermediate CMR was exclusively subepicardial in our group, compared to the classic myocarditis group, which showed a wider variety in patterns of enhancement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our comparison, the classic myocarditis group had a higher burden of LGE than the C-VAM group at intermediate term follow-up. These findings suggest the possibility of a more favorable prognosis in children with C-VAM as opposed to classic myocarditis and extend earlier findings from our group comparing early clinical outcomes among patients with C-VAM, classic myocarditis, and MIS-C(12). The pattern of LGE at intermediate CMR was exclusively subepicardial in our group, compared to the classic myocarditis group, which showed a wider variety in patterns of enhancement.…”
Section: Discussionsupporting
confidence: 88%
“…Many children with classic myocarditis have ventricular systolic dysfunction and myocardial fibrosis that persist beyond the acute phase (7)(8)(9) whereas these findings largely resolve in children with MIS-C (10,11). While the short-term outcomes of COVID-19 vaccine associated myocarditis (C-VAM) have been shown to be less severe than those with classic viral myocarditis or MIS-C (12), the intermediate-term effects are unknown. We aimed 1) to describe the CMR findings of COVID-19 vaccine associated myocarditis patients at intermediate follow up and 2) to compare these findings to those of children with classic myocarditis and MIS-C.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, a recent report comparing classic myocarditis to COVID-19 vaccine-related myocarditis in individuals aged younger than 21 years observed similar clinical presentations and found COVID-19 vaccine-related myocarditis had better outcomes and a more rapid cardiac recovery. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Use of non-steroidal anti-inflammatory drugs, immune globulin (IVIG), and steroids is not common ( 48 ) and remains controversial ( 49 ). A pediatric study comparing drug use in patients with viral MYO, MIS-C MYO and vaccine-related MYO has shown that intravenous immunoglobulin (IVIG) and steroids were frequently used in patients with classic MYO and MIS-C MYO but in only one and in none of the 9 patients with previous COVID-19 immunization ( 50 ). Vasopressors were most often used in patients with traditional viral MYO (42%) or MIS‐C MYO (52%) and rarely used in vaccine‐related MYO (22%), although this difference was not statistically significant.…”
Section: Clinical Characteristics and Outcome Of Myocarditis Associat...mentioning
confidence: 99%